220. Taking Off With Antimicrobial Intervention Rounds (AIR): Successes of a Pilot Stewardship Service at a Tertiary-Care VA Medical Center. (26th November 2018) - Akpoji, Ukwen; Colindres, Roberto Viau; Jump, Robin; Stiefel, Usha
Abstract: Background: Prospective audit and feedback is one of the core strategies of an antimicrobial stewardship program (ASP). Here, we hypothesized that the addition of AIR to our extant ASP would enhance appropriate use of parenteral (IV) antibiotics (ABs) on a large inpatient medical service. Methods: Adult patients on medicine wards beginning in October 2017 and not followed by the infectious diseases (ID) service were included for stewardship intervention if they were on IV ABs ≥48 hours. Recommendations were classified into: (1) duration of therapy; (2) dose adjustment; (3) IV to oral conversion; (4) adverse event prevention; (5) AB avoidance; (6) anti-pseudomonal or (7) vancomycin de-escalation; (8) AB discontinuation; (9) ID consult; (10) Δ alternative AB; (11) allergy assessment; or (12) diagnostics. Early impact of the interventions was assessed after 3 months via the Standardized Antimicrobial Administration Ratio (SAAR) and compared with the 3-month, pre-AIR period. The SAAR is used to benchmark facilities' AB use against those of similar complexity; SAAR = 1 indicates that observed = predicted use. Results: For 158 interventions made, the most common syndromes were pneumonia (41%), skin and soft tissue (29.4%), and urinary tract infection (17.7%). Intervention categories other than 4, 9, and 11 had acceptance rates >85% (Figure 1). The SAAR decreased from the pre- to post-AIR period in terms of agents for: broad-spectrum use in HAI (SAAR relative ratio [RR]: 0.80, 95% CI [0.73–0.88]); MRSA (SAAR RR: 0.81, 95% CI [0.73–0.91]); and all indications (SAAR RR: 0.86, 95% CI [0.82–0.90]). During the same periods, surgical wards without AIR showed no Δ in AB use. Conclusion: The majority of AB use recommendations delivered by a pharmacist–physician stewardship team were highly accepted by medical providers and led to a 15–20% decrease in overall AB use, without adverse effect during the immediate postintervention period. Potential clinical benefits, such as decreased rates of Clostridium difficile disease, will need to be measured as the AIR program advances. It is worth noting that interventions for AB allergy assessment were least accepted by providers, possibly due to time required to comply. Design of prospective audit and feedback programs may need to address this potential deficiency. Disclosures: All authors: No reported disclosures.